Phnom Penh Kaleidoscope: Construction Boom, Material Itineraries and Changing Scales in Urban Cambodia. Issue 2 (3rd April 2021) - Jensen, Casper Bruun
Abstract: Cambodia's urban environments have changed rapidly over the last decades, and perhaps especially over the last few years. After the 2018 election, democracy was widely perceived as eroding. This change created a new context for real-estate investment, which appeared more stable than ever. As investments exploded, the already fast-paced construction business accelerated. Combining an STS focus on distributed agency with an anthropological interest in practices of worlding, this paper analyzes urban transformations in Phnom Penh (and Sihanoukville) as effects of assemblage. Setting in motion new material itineraries, patterned flows of people and things, the construction boom has been felt across the urban spectrum. Modularizing and segmenting cities and filtering populations, these itineraries have also catalyzed changing perspectives on life in the cities, on local and regional relations with "the Chinese, " and on what the future has in store for Cambodia. Interspersing street-level observations and ethnographic materials with media reports and political commentary, I show tuk-tuk drivers, journalists, businessmen, politicians and academic scholars to be simultaneously engaged in assembling the city. Their vastly different projects and practices generate different urban scales – economic, cultural, political, and ethnic – which co-exist, layer, or overlap – incongruently. The resulting image is kaleidoscopic: Phnom Penh kaleidoscope.